2011
DOI: 10.1007/s12630-011-9578-3
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane and desflurane protect cholinergic-induced bronchoconstriction of hyperreactive airways in rabbits

Abstract: Purpose The potential of desflurane to alter respiratory mechanics in the presence of bronchial hyperresponsiveness (BHR) is still a subject of debate. Accordingly, we evaluated the bronchoprotective potential of desflurane compared with sevoflurane following cholinergic lung constriction in rabbits with normal and hyperreactive airways. Methods The input impedance of the respiratory system (Zrs) was measured during midazolam-based anesthesia before and during intravenous infusions of increasing doses of metha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…Sevoflurane is one of the most commonly used volatile anesthetics. Additionally, sevoflurane produces anti-inflammatory and bronchiodilatory effects by unknown mechanisms [ 21 – 23 ]. Some studies showed that sevoflurane inhibited neutrophil function and the production of reactive oxygen species (ROS) in ischemic reperfusion injuries [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sevoflurane is one of the most commonly used volatile anesthetics. Additionally, sevoflurane produces anti-inflammatory and bronchiodilatory effects by unknown mechanisms [ 21 – 23 ]. Some studies showed that sevoflurane inhibited neutrophil function and the production of reactive oxygen species (ROS) in ischemic reperfusion injuries [ 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that volatile anesthetics delivered by mechanical ventilation alleviated lung inflammation by reducing TNF-α and nitric oxide release in rats that had received intratracheal LPS [ 16 20 ]. Sevoflurane is commonly used to sedate patients prior to intubation for mechanical ventilation because of its good controllability [ 21 ]. Recently, additional advantages of sevoflurane have been reported, including dilation of bronchioles and reduction of bronchial hyperresponsiveness in patients with asthma, indicating that it has lung protective effects [ 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, indirect mechanisms associated with prevention of lung volume loss by inhibiting peripheral airway closures might have also contributed to the observed effects of levosimendan on the G and H responses. Interestingly, the ability of levosimendan to prevent MCh-induced elevations in respiratory tissue damping and stiffness is more pronounced than that of the volatile anesthetic agents, where opening the K ATP channels has little (24) or no effect on this lung compartment (17,28). This feature of levosimendan confirms its potent beneficial action on the lung periphery, as outlined above.…”
Section: Systemic Circulatory Effects Of Levosimendanmentioning
confidence: 70%